DAMPAK KEBERADAAN SEKTOR PARIWISATA TERHADAP PENINGKATAN FAKTOR SOSIAL EKONOMI MASYARAKAT KAMPUNG TENUN SAMARINDA DI KOTA SAMARINDA KALIMANTAN TIMUR - Sudarmayasa, I Wayan; Lanang Nala, I Wayan (Jurnal Master Pariwisata (JUMPA); Volume 05, Nomor 02, Januari 2019DO - 10.24843/JUMPA.2018.v05.i02.p04, 2019)
The purpose of this study is to examine the contribution of the impact provided by the existence of tourist destinations on the social and economic influence of the local community's destination. This method uses qualitative descriptive method and purposive sampling method, focuses on the chairman of the business group. The results of this study indicate that there is a synergy between the existence of the tourism sector to improve the economy and social community in tourist destination areas. Keywords : Tourism, Impact, economy, social, Destinations